Small Area Estimation Jumlah Penderita Penyakit TBC di Kabupaten Lombok Timur Menggunakan Metode Empirical Bayes - Toyyibah, Muslimatun; Komalasari, Desy; Fitriyani, Nurul (University of Mataram, 2018)
Empirical Bayes is one of small area estimation method that can be used to predict small area parameters. The small area is defined as a subpopulation of small sample sizes. Empirical Bayes is suitable for use in counted data with Poisson-Gamma model. The purpose of this research was to determine the sub-districts that have the highest risk in the number of people with TBC disease in East Lombok Regency. Based on the results, the analysis showed that sub-districts with the highest risk were Sukamulia Sub-district with 1.65543 value of relative risk in 2014, Sambelia Sub-district with 1.80396 value of relative risk in 2015, and Sambelia Sub-district with 4.12718 values ov relative risk in 2016.